Cosmological measurements from angular power spectra analysis of BOSS DR12 tomography. Issue 1 (22nd January 2019) - Loureiro, Arthur; Moraes, Bruno; Abdalla, Filipe B; Cuceu, Andrei; McLeod, Michael; Whiteway, Lorne; Balan, Sreekumar T; Benoit-Lévy, Aurélien; Lahav, Ofer; Manera, Marc; Rollins, Richard P; Xavier, Henrique S
ABSTRACT: We constrain cosmological parameters by analysing the angular power spectra of the Baryon Oscillation Spectroscopic Survey DR12 galaxies, a spectroscopic follow-up of around 1.3 million SDSS galaxies over 9376 deg 2 with an effective volume of ∼6.5 (Gpc h −1 ) 3 in the redshift range 0.15 ≤ z < 0.80. We split this sample into 13 tomographic bins (Δz = 0.05); angular power spectra were calculated using a Pseudo- C ℓ estimator, and covariance matrices were estimated using lognormal simulated maps. Cosmological constraints obtained from these data were combined with constraints from Planck cosmic microwave background experiment as well as the JLA supernovae compilation. Considering a w CDM cosmological model measured on scales up to k max = 0.07 h Mpc −1, we constrain a constant dark energy equation-of-state with an 4 per cent error at the 1σ level: w_0 = -0.993^+0.046_-0.043, together with Ωm = 0.330 ± 0.012, Ωb = 0.0505 ± 0.002, S_8 σ _8 Ω _ m/0.3 = 0.863 ± 0.016, and h = 0.661 ± 0.012. For the same combination of data sets, but now considering a ΛCDM (lambda cold dark matter) model with massive neutrinos and the same scale cut, we find Ωm = 0.328 ± 0.009, Ω _ b = 0.05017^+0.0009_-0.0008, S 8 = 0.862 ± 0.017, and h = 0.663^+0.006_-0.007, and a 95 per cent credible interval (CI) upper limit of ∑ m ν < 0.14 eV for a normal hierarchy. These results are competitive if not better than standard analyses with the same data set, and demonstrate that this should be a method of choice for future surveys, opening the door for their full exploitation in cross-correlation probes.